Longing for Belonging: Forwarding Andrew Walls’ Thoughts on Migration and Mission through an Ethnographic Study on Diasporic Chinese in Singapore's Christian Communities - Jia Chyi Hwang, Jackie (Studies in world christianity, 2023)
This study on migration and Chinese Christianity uncovers both the potential and limitations in the late Professor Andrew Walls’ conception of how migration shapes global Christianity. Using an ethnographic approach, I examine how international students from China engaged in a quest for jia (home, family, belonging) by interacting with Singapore's Chinese Christian communities. For these students from China and the Singaporean Chinese Christians who encounter them, the personal narratives on both sides exhibit three traits: (1) a give-and-take relationship between different notions of ‘Chineseness’, (2) a transnational sense of family, and (3) an understanding of ecclesiology that is under negotiation. The ethnographic profile of Chinese hybridity that emerges shows how Walls’ ideas can be refined by a better understanding of co-ethnic Chinese Christianity which lies beyond China's geopolitical boundaries.